Exploring Islamic Boarding School Students’ Attitudes in English Conversation Habit - Asgara, Eqy Yudha; Ahmad, Yousef Bani; Utami, Praditya Putri (STKIP Yapis Dompu, 2022)
The narrative inquiry research was conducted to explore islamic boarding school students’ attitudes in using English conversation habits and to find out the opportunities and challenges that they faced when learning English using it during boarding school. The data were collected from four islamic boarding school students’ of a state boarding school in Karawang, Indonesia through semistructured interviews and questionnaires. Thematic analysis was used in analyzing the data. The results revealed that islamic boarding school felt very interested, happy, and are motivated to use English conversation habits since English conversation habits is considered quite effective and flexible in terms of time and place, especially in terms of increasing students creativity and productivity, helping students practice English, and providing learning experiences using a new learning system. However, islamic boarding school students’ also felt challenged and worried to face several obstacles that’s occurred such as lack of student participation, pronunciation is difficult, and some students even feel insecure. Therefore, Islamic boarding school students are still interested in carrying out classroom learning with English conversation habits in the future. In conclusion, the majority of Islamic boarding school students' had a positive attitude towards the use of English conversation habits since it was considered one of the best learning program that students can use while teaching English during boarding school.